Non-pre-crosslinking type white EVA (Ethylene Vinyl Acetate) adhesive film and application thereof

By adding specific components to the white EVA film, a non-precrosslinked white EVA low-acid film was prepared, which solved the problem of increased hardness by overturning and pre-crosslinking during lamination, and achieved a high adhesion and low water permeability film, which significantly improved the efficiency and reliability of the components.

CN119614084APending Publication Date: 2025-03-14CSI SOLAR POWER GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311180212.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing white EVA packaging film is prone to overflow and flanges when laminated, causing the battery to be contaminated and covered, affecting the appearance of the component and power generation efficiency. In addition, the pre-crosslinking method increases the hardness of the film, which may cause cryptic cracks or displacement, and lead to delamination in humid and heat environments.

Method used

A non-pre-crosslinked white EVA low-acid adhesive film is used, and polyethylene, titanium dioxide, crosslinking agent, anti-hydrolyzer, silane, acid absorbent, acrylate, light stabilizer and antioxidant are added. Through the combination of these components, the water permeability of the adhesive film is reduced, the adhesion and water barrier are improved, and the glue is overflowed and flanked.

Benefits of technology

The adhesive film can maintain a high bonding force after 2000 hours of humidity and heat. The yellowing value after UV and humidity and heat aging is small, and the acetic acid content is low. It can ensure the efficiency of the components for a long time and reduce the scrap rate of the components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004446984960000031
    Figure BDA0004446984960000031
  • Figure BDA0004446984960000071
    Figure BDA0004446984960000071
  • Figure BDA0004446984960000072
    Figure BDA0004446984960000072
Patent Text Reader

Abstract

The invention provides a non-pre-crosslinking type white EVA adhesive film and application thereof. The non-pre-crosslinking type white EVA adhesive film is prepared from the following components: EVA particles, polyethylene, titanium dioxide, a crosslinking agent, an anti-hydrolysis agent, silane, an acid acceptor, acrylate, a light stabilizer and an antioxidant. Compared with a pre-crosslinking type white EVA adhesive film, the adhesive film provided by the invention has the advantages that the water permeability is reduced, the adhesive film can still keep relatively high adhesive force with glass after being moistened for 2000 hours, the yellowing value is relatively small after UV and damp-heat aging, the acetic acid content is low, and the use efficiency of an assembly can be ensured for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells and relates to a non-pre-crosslinked white EVA adhesive film and applications thereof, in particular to a non-pre-crosslinked white EVA low-acid adhesive film and applications thereof. Background Art

[0002] In recent years, white EVA encapsulation film has been widely used in various types of component products as a mainstream product in the market. As a base film, it can improve the reflectivity, effectively improve the utilization rate of sunlight, and reduce the packaging loss of the component.

[0003] However, due to its own characteristics, white adhesive film is prone to overflow and flanging onto the front solar cell during lamination, causing contamination and coverage of the solar cell, seriously affecting the appearance and power generation efficiency of the module. The industry generally uses pre-crosslinking to partially irradiate the adhesive film before lamination to form a cross-linked network structure to reduce shrinkage during lamination and reduce the probability of overflow and flanging.

[0004] However, this method also has certain disadvantages: the network structure formed by preferential pre-crosslinking increases the hardness of the film at the beginning of lamination to a certain extent, which can easily cause hidden cracks or displacement of the battery cell; furthermore, the degree of pre-crosslinking is generally controlled at more than 30%, and the premature reaction of additives can easily cause insufficient adhesion, which can easily cause delamination between the film and the backplane or the battery cell under conditions of humidity, heat, ultraviolet rays, etc., resulting in the scrapping of the component.

[0005] Moreover, the introduction of titanium dioxide has weakened the film's ability to isolate water vapor, its volume resistivity and corrosion resistance to a certain extent. However, since it is very susceptible to corrosion by water vapor, polar water molecules will attack the direct van der Waals force or hydrogen bond between the glass and EVA, causing it to fail and lead to delamination. At the same time, water vapor can also cause the formation of vinyl acetate under the combination of light, oxygen, etc., to hydrolyze or break, forming small molecules such as acetic acid, aldehydes, and ketones, causing corrosion to the battery cells.

[0006] Therefore, it is desired in the art to develop an EVA film which not only has good bonding properties and low water permeability but also can avoid the defects of the existing EVA packaging films. Summary of the invention

[0007] In view of the deficiencies of the prior art, the object of the present invention is to provide a non-pre-crosslinked white EVA adhesive film and its application, and in particular to provide a non-pre-crosslinked white EVA low-acid adhesive film and its application. Compared with the pre-crosslinked white EVA adhesive film, the adhesive film provided by the present invention has a lower water permeability, can still maintain a high adhesion with glass after 2000h of wet heat, has a smaller yellowing value after UV and wet heat aging, has a low acetic acid content, and can ensure the use efficiency of the components for a long time.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a non-pre-crosslinked white EVA film, wherein the raw materials for preparing the non-pre-crosslinked white EVA film include the following components: EVA particles, polyethylene, titanium dioxide, a crosslinking agent, an anti-hydrolysis agent, silane, an acid absorber, acrylate, a light stabilizer and an antioxidant.

[0010] In the present invention, the addition of polyethylene can reduce the melt index of EVA, reduce fluidity, ensure that the film does not turn over during lamination, and reduce the probability of glue overflow, so the pre-crosslinking process can be omitted, reducing costs while improving production efficiency; and the addition of polyethylene can improve polarity and increase the hydrophobicity of the film, so that it has a lower water permeability, and combined with acrylic ester to increase the crosslinking density, the water barrier of the overall film is greatly increased, preventing the water vapor permeability during use, and maintaining the normal operation of the battery cell. The addition of silane can greatly increase the bonding strength between the film and the glass and maintain it for a long time. The anti-hydrolysis agent can inhibit the hydrolysis of the EVA segment to the greatest extent, avoid the generation of acidic substances, and compound the acid absorber to adsorb the free acidic substances in the film. The anti-hydrolysis agent can be used for polymer materials containing ester bonds, etc., and can remove acid and water to prevent the degradation of its own segments. The acid absorber can adsorb the free acidic impurities in the auxiliary agent and the acidic substances generated by the degradation of the EVA segment, produce stable compounds, and reduce corrosion to the battery cell.

[0011] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film include the following components in parts by weight:

[0012]

[0013] Preferably, the raw materials for preparing the non-pre-cross-linked white EVA film are measured in parts by weight, and the amount of EVA particles used can be 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, etc.

[0014] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film are measured in parts by weight, and the amount of polyethylene used can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.

[0015] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film can include 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, etc. of titanium dioxide in terms of weight parts.

[0016] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film can be used in an amount of 0.8 parts, 0.9 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc. of the crosslinking agent in parts by weight.

[0017] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film can include 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc., in terms of weight parts.

[0018] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film can contain 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc. of silane in terms of weight parts.

[0019] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film can be used in an amount of 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc., based on weight parts.

[0020] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film can include 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc., in terms of weight parts.

[0021] Preferably, the amount of the light stabilizer used in the preparation of the non-pre-crosslinked white EVA film can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, etc., based on the weight parts of the raw materials.

[0022] Preferably, the raw materials for preparing the non-pre-crosslinked white EVA film can be used in an amount of 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, etc., based on weight parts.

[0023] Preferably, the polyethylene comprises linear low density polyethylene and / or low density polyethylene.

[0024] Preferably, the titanium dioxide includes rutile titanium dioxide, for example, any one of Longbai 886, Panhua DR-2588, and CITIC CR-210, or a combination of at least two thereof.

[0025] Preferably, the crosslinking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, triallyl isocyanurate, triallyl cyanurate, diisopropylbenzene peroxide, benzoyl peroxide, di-tert-butyl peroxide or diisopropylbenzene hydroperoxide, or a combination of at least two thereof.

[0026] Preferably, the anti-hydrolysis agent comprises carbodiimide and / or polycarbodiimide.

[0027] Preferably, the silane includes any one or a combination of at least two of isocyanatepropyltrioxyethylsilane, vinyltriacetoxysilane, methacryloxypropyltrimethoxysilane derivatives, small molecule polysiloxane or mercaptosilane derivatives.

[0028] Preferably, the acid absorbent comprises Mg4Al2(OH) 12 CO3·3H2O、Mg 15 Zn 0.5 Al2(OH) 12 CO·3H2O、Mg 4.5 Al2(OH) 13 CO3·3.5H2O、Mg6Al2(OH) 16 CO3·3H2O、Mg 15 Zn 0.5 Al2(OH) 12 CO3、Mg6Al2(OH) 16 CO3 or Mg 4.5 Al2(OH) 13 Any one or a combination of at least two of CO3.

[0029] Preferably, the acrylate includes any one of ethoxylated trimethylolpropane triacrylate, propoxylated trimethylol triacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol diacrylate, tricyclohexane dimethanol diacrylate or ditrimethylolpropane tetraacrylate, or a combination of at least two thereof.

[0030] Preferably, the light stabilizer includes any one or a combination of at least two of a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis-2,2,6,6-tetramethylpiperidinol sebacate, a hindered amine light stabilizer, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(2,4-di-tert-butylphenyl) phosphite or 2,2,6,6-tetramethyl-4-piperidinyl ester.

[0031] Preferably, the antioxidant comprises any one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris[2,4-di-tert-butylphenyl]phosphite or a combination of at least two thereof.

[0032] Preferably, the thickness of the non-pre-crosslinked white EVA film is 500-700 μm, for example, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, etc.

[0033] The present invention does not limit the preparation method of the non-pre-crosslinked white EVA film, and it can be prepared by existing conventional methods. For example, the non-pre-crosslinked white EVA film of the present invention can be obtained by mixing, screw plasticizing, die co-extrusion, and cast compounding.

[0034] In a second aspect, the present invention provides a use of the non-pre-crosslinked white EVA film as described in the first aspect in a photovoltaic module.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] In the present invention, the addition of polyethylene can reduce the melt index of EVA, reduce fluidity, ensure that the film does not turn over during lamination, and reduce the probability of glue overflow, so the pre-crosslinking process can be omitted, reducing costs while improving production efficiency; and the addition of polyethylene can improve polarity and increase the hydrophobicity of the film, so that it has a lower water permeability, combined with acrylate to increase the crosslinking density, so that the water barrier of the overall film is greatly increased, preventing the water vapor permeability during use, and maintaining the normal operation of the battery cell. The addition of silane can greatly increase the bonding strength between the film and the glass and maintain it for a long time. The anti-hydrolysis agent can inhibit the hydrolysis of the EVA segment to the greatest extent, avoid the generation of acidic substances, and at the same time compound the acid absorber to adsorb the free acidic substances in the film. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] The information of some raw materials used in the examples and comparative examples of the present invention is as follows:

[0039] Linear low-density polyethylene: ExxonMobil 6101;

[0040] Low density polyethylene: Nexxstar TM Low EVA-00111;

[0041] Carbodiimide: Shanghai Langyi 1010;

[0042] Polycarbodiimide: Shanghai Langyi 210;

[0043] Methacryloyloxypropyltrimethoxysilane derivatives: J&Y LA-570 Shanghai Lanthanum Chemical;

[0044] Succinic acid, polymer with 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol: Newshow Chemical UV-622.

[0045] Example 1

[0046] In this embodiment, a non-pre-crosslinked white EVA film is provided, and the thickness is 600 μm. The raw materials and amounts of the non-pre-crosslinked white EVA film are shown in Table 1.

[0047] Table 1

[0048]

[0049]

[0050] The preparation method comprises the following steps:

[0051] The above-prepared raw materials are blended, then plasticized by a screw, and co-extruded and cast by a die to obtain the non-pre-crosslinked white EVA film.

[0052] Example 2

[0053] In this embodiment, a non-pre-crosslinked white EVA film is provided, and the thickness is 600 μm. The raw materials and amounts of the non-pre-crosslinked white EVA film are shown in Table 2.

[0054] Table 2

[0055]

[0056] The preparation method is the same as Example 1.

[0057] Example 3

[0058] In this embodiment, a non-pre-crosslinked white EVA film is provided, and the thickness is 600 μm. The raw materials and amounts of the non-pre-crosslinked white EVA film are shown in Table 3.

[0059] Table 3

[0060]

[0061] The preparation method is the same as Example 1.

[0062] Example 4

[0063] In this embodiment, a non-pre-crosslinked white EVA film is provided, and the thickness is 600 μm. The raw materials and amounts of the non-pre-crosslinked white EVA film are shown in Table 4.

[0064] Table 4

[0065]

[0066]

[0067] The preparation method is the same as Example 1.

[0068] Example 5

[0069] In this embodiment, a non-pre-crosslinked white EVA film is provided, and the thickness is 600 μm. The raw materials and amounts of the non-pre-crosslinked white EVA film are shown in Table 5.

[0070] Table 5

[0071]

[0072] The preparation method is the same as Example 1.

[0073] Example 6

[0074] The only difference between this embodiment and embodiment 1 is that silane is replaced by an equal amount of isobutyltriethoxysilane.

[0075] Example 7

[0076] The difference between this embodiment and embodiment 1 is that Mg4Al2(OH) 12 CO3·3H2O and Mg 4.5 Al2(OH) 13 The weight percentage of CO3·3.5H2O is 0.05 parts.

[0077] Example 8

[0078] The difference between this embodiment and embodiment 1 is that Mg4Al2(OH) 12 CO3·3H2O and Mg 4.5 Al2(OH) 13 The weight percentage of CO3·3.5H2O is 0.6 parts.

[0079] Comparative Example 1

[0080] The only difference between this comparative example and Example 1 is that the preparation raw materials do not include an acid absorbent.

[0081] Comparative Example 2

[0082] The only difference between this comparative example and Example 1 is that polyethylene is not included in the preparation raw materials.

[0083] Comparative Example 3

[0084] The only difference between this comparative example and Example 1 is that acrylate is not included in the preparation raw materials.

[0085] Comparative Example 4

[0086] The only difference between this comparative example and Example 1 is that no anti-hydrolysis agent is included in the preparation raw materials.

[0087] The non-pre-crosslinked white EVA film provided in the embodiment and the comparative example was subjected to a performance test, and the test method was as follows:

[0088] (1) Water permeability: tested in accordance with ISO 15106-1:2003(E);

[0089] (2) Initial bonding strength with the back sheet: Test the flexible material against the rigid material in accordance with GB / T 2790-1995 Adhesive 180 peel strength test method;

[0090] (3) Bonding strength with back sheet after DH2000h: Test the flexible material against the rigid material according to GB / T 2790-1995 Adhesive 180 peel strength test method;

[0091] (4) Δb (UV200h): tested in accordance with GB / T 29848-2018 Ethylene-vinyl acetate copolymer (EVA) adhesive film for photovoltaic module encapsulation materials;

[0092] (5) Δb (DH2000h): Tested in accordance with GB / T 29848-2018 Ethylene-vinyl acetate copolymer (EVA) film for photovoltaic module encapsulation materials;

[0093] (6) Volume resistivity: Tested in accordance with GB / T 1401-2006 Test methods for volume resistivity and surface resistivity of solid insulating materials;

[0094] (7) Acetic acid content (after cross-linking): tested according to ISO15106-1:2003(E)Plastics-Film and sheeting-Determination of water vapour transmission rate;

[0095] (8) Module power degradation: The test is carried out in accordance with IEC TS 62804-1:2015 Crystalline silicon photovoltaic module potential induced degradation test method.

[0096] The performance test results are shown in Table 6.

[0097] Table 6

[0098]

[0099] It can be seen from Table 6 that the non-pre-crosslinked white EVA films provided in Examples 1-5 of the present invention all have good bonding strength (initial bonding strength with the back sheet: 89.39-101.31 N / cm, bonding strength with the back sheet after DH2000h: 72.16-87.52 N / cm) and lower water permeability (14.29-16.32 g / m 2 .d).

[0100] Compared with Example 1, the white EVA film provided in Example 6 is delaminated from the backboard DH2000h, the acetic acid content of the white EVA film provided in Example 7 is significantly increased after cross-linking, and the water permeability of the white EVA film provided in Example 8 is increased.

[0101] Compared with Example 1, the acetic acid content of the cross-linked white EVA film provided in Comparative Example 1 is significantly increased, the water permeability of the white EVA films provided in Comparative Examples 2-3 is increased, and the acetic acid content of the cross-linked white EVA film provided in Comparative Example 1 is slightly increased.

[0102] In summary, the EVA particles of the present invention add 10-20% of ethylene-modified resin to reduce the melting value of EVA and reduce fluidity; ensure that the film does not turn over during lamination, and reduce the probability of glue overflow; therefore, the pre-crosslinking process can be omitted, reducing costs while improving production efficiency. It can also improve polarity and increase the hydrophobicity of the film, making it have a lower water permeability, and combined with compounded acrylic ester to increase the crosslinking density, so that the water barrier of the overall film is greatly increased, preventing the water vapor permeability during use and maintaining the normal operation of the battery cell.

[0103] The anti-hydrolysis agent can inhibit the hydrolysis of the EVA chain segment to the greatest extent, avoiding the generation of acidic substances, and the compound acid absorber can absorb the free acidic substances in the film. The acid absorber can absorb the free acidic impurities in the auxiliary agent and the acidic substances generated by the degradation of the EVA chain segment, produce stable compounds, and reduce the corrosion to the battery cell.

[0104] Performance test results of actual embodiments show that, compared with the pre-crosslinked white EVA film of the same industry, the water permeability of the film involved in the present invention is reduced by more than 20%, and it can still maintain a high adhesion with the glass after 2000 hours of wet heat aging. The yellowing value after UV and wet heat aging is also much smaller than that of the same industry products, and the acetic acid content is more than 50% lower, which can ensure the efficiency of the component for a long time.

[0105] The applicant declares that the present invention illustrates the non-pre-crosslinked white EVA film and its application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A non-pre-crosslinked white EVA film, characterized in that: The raw materials for preparing the non-pre-crosslinked white EVA adhesive film include the following components: EVA particles, polyethylene, titanium dioxide, a crosslinking agent, an anti-hydrolysis agent, silane, an acid absorber, acrylate, a light stabilizer and an antioxidant.

2. The non-pre-crosslinked white EVA film according to claim 1, characterized in that: The raw materials for preparing the non-pre-crosslinked white EVA film include the following components in parts by weight:

3. The non-pre-crosslinked white EVA film according to claim 1 or 2, characterized in that: The polyethylene includes linear low-density polyethylene and / or low-density polyethylene; Preferably, the titanium dioxide comprises rutile titanium dioxide.

4. The non-pre-crosslinked white EVA film according to any one of claims 1 to 3, characterized in that: The crosslinking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, triallyl isocyanurate, triallyl cyanurate, diisopropylbenzene peroxide, benzoyl peroxide, di-tert-butyl peroxide or diisopropylbenzene hydroperoxide, or a combination of at least two thereof.

5. The non-pre-crosslinked white EVA film according to any one of claims 1 to 4, characterized in that: The anti-hydrolysis agent includes carbodiimide and / or polycarbodiimide; Preferably, the silane includes any one or a combination of at least two of isocyanatepropyltrioxyethylsilane, vinyltriacetoxysilane, methacryloxypropyltrimethoxysilane derivatives, small molecule polysiloxane or mercaptosilane derivatives.

6. The non-pre-crosslinked white EVA film according to any one of claims 1 to 5, characterized in that: The acid absorbent includes Mg4Al2(OH) 12 CO3·3H2O、Mg 15 Zn 0.5 Al2(OH) 12 CO·3H2O、Mg 4.5 Al2(OH) 13 CO3·3.5H2O、Mg6Al2(OH) 16 CO3·3H2O、Mg 15 Zn 0.5 Al2(OH) 12 CO3、Mg6Al2(OH) 16 CO3 or Mg 4.5 Al2(OH) 13 Any one or a combination of at least two of CO3.

7. The non-pre-crosslinked white EVA film according to any one of claims 1 to 6, characterized in that: The acrylate includes any one of ethoxylated trimethylolpropane triacrylate, propoxylated trimethylol triacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol diacrylate, tricyclohexane dimethanol diacrylate or ditrimethylolpropane tetraacrylate, or a combination of at least two thereof.

8. The non-pre-crosslinked white EVA film according to any one of claims 1 to 7, characterized in that: The light stabilizer includes any one or a combination of at least two of a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis-2,2,6,6-tetramethylpiperidinol sebacate, a hindered amine light stabilizer, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(2,4-di-tert-butylphenyl) phosphite or 2,2,6,6-tetramethyl-4-piperidinyl ester; Preferably, the antioxidant comprises any one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris[2,4-di-tert-butylphenyl]phosphite or a combination of at least two thereof.

9. The non-pre-crosslinked white EVA film according to any one of claims 1 to 8, characterized in that: The thickness of the non-pre-crosslinked white EVA film is 500-700 μm.

10. Use of the non-pre-crosslinked white EVA film according to any one of claims 1 to 9 in a photovoltaic module.